Characterisation of central versus peripheral tumour associated macrophages in glioblastoma multiforme. (25th February 2016) - Youshani, Amir Saam; Yu, Kenny; O'Leary, Claire; Pathmanaban, Omar; Kamaly-Asl, Ian; Bigger, Brian
Abstract: Background: Glioblastoma multiforme is the most biologically aggressive brain tumour, with only 12 month survival, despite maximum treatment. Tumour-associated macrophages and microglia (TAMM) are myeloid cells populating 30–50% of glioblastoma multiforme tumours and are identified as potential immunotherapy targets. However, characterising functional roles of TAMM subpopulations remains elusive, because of flawed mouse models and inadequate cell-surface markers. In normal rodent brain, antibody markers CD11bhi and CD45hi are proposed to highlight infiltrating monocytes, whereas CD11bhi and CD45lo cells represent microglia and differentiated peripheral macrophages. This marker-set provides conflicting results in the context of the tumour microenvironment. We redressed this issue and aimed to determine whether peripheral or central TAMMs have independent roles in glioblastoma multiforme. Methods: With our non-myeloablative bone-marrow transplant model, we can replace a mouse immune system using congenic donor cells marked with green fluorescence protein (GFP) without damaging the blood-brain barrier or inadvertently activating microglia; when applying this technique we subsequently distinguish between central microglial and peripheral macrophage populations. By stereotaxic intracranial implantation of murine glioblastoma multiforme (GL261), we recapitulated the normal development of a glioblastoma multiforme tumour and performed sham intracranial injections as a comparative control. Fluorescence-activated cell sorting was done to separate TAMM subpopulations for RNA sequencing. Findings: Our chimeric mouse model consistently produced 70–80% peripheral blood chimerism and overcame the issue surrounding cell-surface expression markers, distinguishing peripherally infiltrating and central tissue-resident brain cells by GFP marker status. Cerebral digestion and analysis of tumour-implanted mice revealed a novel third population (FSChi/SSChi cells) on flow cytometry that stained greater than 90% CD11b/CD45+ suggestive of TAMMs; but this cell population was absent in hemispheres of both non-tumour bearing and sham-injected mice. Interpretation: Our preliminary data showed that in chimeric mice implanted with glioblastoma multiforme, peripheral cells (GFP high) were the dominant infiltrating population. With RNA extraction for downstream transcriptional analysis we aim to reliably track trafficking myeloid populations and subsequently address the ambiguity surrounding TAMMs. Thereafter, we aim to develop an immunotherapy against glioblastoma multiforme using the findings from our study. Funding: None.